Технология прямой оценки эффективности процессов управления - Луценко, Игорь Анатольевич; Николаенко, Наталья Игоревна; Гнатюк, Юлия Игоревна (Eastern-European Journal of Enterprise Technologies, 2009)
The technology for straight value of effectiveness closed controlling system is cultivate. With the utilization of developed technology were research main activities, that are in use as a basic generalized optimality criterion. On the basic of experimental inverstigations was realized the choice of optimality criteria.